Characterization and transfer of antimicrobial resistance in lactic acid bacteria from fermented dairy products in China - Yang, Chao; Yu, Tao (The Journal of Infection in Developing Countries, 2019)
Introduction: Lactic acid bacteria (LAB) are commonly found in foods and are also natural intestinal inhabitants in humans and most animals. However, information regarding antimicrobial resistance and the transfer of resistance genes of LAB from fermented dairy products in China is limited. Methodology: In this study, LAB isolates (n = 82) of Lactobacillus (n = 43) and Streptococcus thermophilus (n = 39) were isolated from 51 commercial fermented food samples in China. All isolates were subjected to pulsed-field gel electrophoresis (PFGE), antimicrobial susceptibility, detecting resistance genes, as well as investigating the transferability of resistance genes. Results: The 43 Lactobacillus isolates yielded 24 PFGE patterns and the 34 isolates of S. thermophilus generated 32 different PFGE patterns. Among the 43 Lactobacillus strains, the most commonly observed resistance was that to streptomycin (83.7%) and gentamycin (83.7%). Among the 39 S. thermophilus strains, the most frequently observed resistance was that to streptomycin (92.3%), gentamycin (87.2%), ciprofloxacin (79.5%), and chloramphenicol (71.8%), whereas the lowest level of resistance was that against erythromycin (7.7%). Antimicrobial resistance genes for erythromycin (emrB), gentamycin (aac(6')-aph(2")), streptomycin (ant(6)), sulfamethoxazole (sulI and sulII), tetracycline (tetM and tetS) were detected in the 18 resistance LAB strains. Conjugation experiments showed that tetM from L. delbrueckii subsp. bulgaricus R6 and tetS from L. plantarum R41 were successfully transferred to L. monocytogenes by filter mating. Conclusions: LAB strains could potentially act as reservoirs of resistance genes and play an active role in the transfer of resistance to humans via the food chain.